1999
DOI: 10.1097/00001756-199908020-00012
|View full text |Cite
|
Sign up to set email alerts
|

Responses of microglia and neural progenitors to mechanical brain injury

Abstract: Neural cells have distinct responses to CNS injury; however, neural progenitor response to CNS injury is not yet documented. Stab injury combined with injection of bromodeoxyuridine (BrdU), a thymidine analog, into adult rat cortex above the lateral ventricle for 10 min resulted in activated microglia/macrophage infiltration along with nuclear factor kappa B (NF kappa B)/p65 activation at the lesion site. Most NF kappa B/p65+ cells displayed a phagocytic morphology. Under these conditions, profound cell apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 11 publications
1
29
0
1
Order By: Relevance
“…Previous studies have shown that there is an increased proliferation of precursor cells in this zone after injury (Weinstein et al, 1996;Tseng and Wu, 1999;Jin et al, 2001). Interestingly, we found MIB5-IR cells in close apposition to Mts1-positive astrocytes with low levels of GFAP, as well as to intensely GFAPlabeled cells, which did not express Mts1.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that there is an increased proliferation of precursor cells in this zone after injury (Weinstein et al, 1996;Tseng and Wu, 1999;Jin et al, 2001). Interestingly, we found MIB5-IR cells in close apposition to Mts1-positive astrocytes with low levels of GFAP, as well as to intensely GFAPlabeled cells, which did not express Mts1.…”
Section: Discussionmentioning
confidence: 94%
“…Stroke elicits a robust response in the SVZ (Arvidsson et al, 2002) and it is not clear if a similar response is seen after stab wound injury (Synowitz et al, 2006;Tzeng and Wu, 1999). As such, the different cellular responses observed in response to injury may underlie the differences reported.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a known mechanism for ischemia-induced neurogenesis and because possible mechanisms include trans-synaptic and diffusible chemical effects, it is unclear if either finding should be surprising. Contralateral electrical, chemical, and vascular effects of hemispheric ischemia are well described, and bilateral induction of neurogenesis by a unilateral stimulus has been reported (22,43). Unilateral stimulation of the perforant path, leading to focal seizure discharges without neuronal injury, increases neurogenesis in the SGZ both ipsilateral and contralateral to the stimulated side (22), and traumatic injury to the cerebral cortex increases BrdUrd labeling in the SVZ bilaterally (43).…”
Section: Discussionmentioning
confidence: 99%
“…Contralateral electrical, chemical, and vascular effects of hemispheric ischemia are well described, and bilateral induction of neurogenesis by a unilateral stimulus has been reported (22,43). Unilateral stimulation of the perforant path, leading to focal seizure discharges without neuronal injury, increases neurogenesis in the SGZ both ipsilateral and contralateral to the stimulated side (22), and traumatic injury to the cerebral cortex increases BrdUrd labeling in the SVZ bilaterally (43). Because transplanted neural stem cells can migrate into tumors from the contralateral hemisphere (44), endogenous neuronal precursors might be expected to proliferate in response to contralateral ischemia as well.…”
Section: Discussionmentioning
confidence: 99%